Effects of Captivity and Season on the Gut Microbiota of the Brown Frog (Rana dybowskii) - Tong, Qing; Liu, Xiao-Ning; Hu, Zong-Fu; Ding, Jia-Feng; Bie, Jia; Wang, Hong-Bin; Zhang, Jian-Tao (Frontiers in Microbiology, 2019)
The gut microbiota of amphibians is affected by exogenous and endogenous factors. We performed a comprehensive analysis using high-throughput sequencing technology and functional predictions and observed general changes in the gut microbiota of frogs in different growth stages, seasons, and growth environments. There were no significant differences in microbial richness and diversity between juvenile and adult wild frogs, between the summer and autumn groups of captive frogs, or between wild and captive frogs. There were significant differences in the gut microbiota community structure of Rana dybowskii between the summer and autumn groups of captive frogs and between wild and captive R. dybowskii, whereas the differences between juvenile and adult wild frogs were not significant. The dominant gut bacterial phyla in frogs from both captive and wild environments included Firmicutes, Bacteroidetes, Proteobacteria and Actinobacteria. Linear discriminant effect size (LEfSe) analysis showed that Bacteroidetes and Firmicutes were significantly enriched in captive and wild R. dybowskii, respectively (LDA>4). The core operational taxonomical units (OTUs) that were found in >90% of all frogs tested encompassed 15 core OTUs. The captive frogs exhibited 15 core OTUs in addition to the above overall core microbiota, whereas the wild frogs exhibited 19 core OTUs in addition to the above overall core microbiota. Predictions made using Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUSt) suggested that eleven KEGG pathways, such as infectious diseases, immune system diseases, metabolism, metabolism of other amino acids, metabolism of cofactors and vitamins, metabolism of terpenoids and polyketides, neurodegenerative diseases, and transport and catabolism, were enriched in captive frogs. The relative abundance of several red-leg-syndrome-related pathogens increased significantly in captive frogs compared with that in wild frogs. To our knowledge, this is the first study of the effects of individual seasons and captivity on the gut microbiota of frogs.